ANALISIS PEMANFAATAN LABORATORIUM IPA DI MADRASAH TSANAWIYAH NEGERI 1 KAMPAR - Juni Harja, Endra; Rahma Primadani Putri; Karlina; Meirisa Dahlia; Royan Nurchoman; M.Rahmad; Roza Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The science laboratory plays an important role in supporting science learning through practical activities that can improve students’ science process skills, conceptual understanding, and critical thinking abilities. However, the utilization of science laboratories in schools still faces various challenges, causing their functions to be less than optimal. This study aimed to analyze the utilization of the science laboratory at MTs Negeri 1 Kampar based on the aspects of planning, organizing, implementation, monitoring, and evaluation. The study employed a qualitative descriptive approach using a case study design. Data were collected through observations, semi-structured interviews, and documentation involving the principal, laboratory coordinator, and science teachers. Data were analyzed descriptively to provide a comprehensive understanding of laboratory utilization. The findings revealed that the utilization of the science laboratory at MTs Negeri 1 Kampar has not been optimal. In terms of planning, practical schedules were not systematically arranged, the procurement of laboratory equipment and materials was not conducted regularly, and standard operating procedures (SOPs) were not consistently implemented. Regarding organization, the laboratory manager also served as a science teacher, resulting in less effective laboratory management. In the implementation aspect, practical activities were limited due to inadequate facilities, equipment, materials, and laboratory conditions. Furthermore, monitoring and evaluation activities were not conducted regularly and lacked proper documentation. Therefore, improvements in laboratory management are needed through the provision of competent laboratory personnel, optimization of laboratory facilities and infrastructure, consistent implementation of SOPs, and strengthening of monitoring and evaluation systems to support the quality of science learning.